Publication Ethics and Publication Malpractice Statement - Board, Editorial (Journal of Scientific Research, 2013)
Journal of Scientific Research (JSR) is committed to maintaining the highest ethical standards. In order to ensure the outcome of providing our readers with an academic journal of high quality, JSR is guided by standard publication Ethics (These guidelines are based on existing Elsevier policies and COPEs Best Practice Guidelines forJournal Editors).